La séparation des Églises et de l’État aux États-Unis : origines et évolution - Mokhtar BEN BARKA (E-REA)
Since the 1970s, religion has made its presence strongly felt in the U. S. political arena. Presidents Jimmy Carter, Ronald Reagan, Bill Clinton, and George W. Bush, self-identified Evangelicals, used to mention their faiths and to include religious references in their speeches.Signaled by the intense campaigns focused on turning Judeo-Christian principles of morality into law, as well as the increasing presence of Evangelicals in the higher spheres of power, the extraordinary “spiritualization” of American politics has urgently revived the debate over secularism. In fact, many observers believe that the influence of the Christian Right and conservative Evangelicals on both home and foreign policy undermines the democratic safeguards pertaining to the American political system. Others are so worried that they set out to combat the Christian Right, seen as a menace to secularism and democracy.Contrary to the belief held by right-wing Evangelicals, the United States is not a Christian nation. The democratic principles set forth in the federal Constitution are not rooted in any particular religion. The Founding Fathers intended to set up an impassable wall between Church and State, with the view of creating a secular republic. Secularism, commonly referred to in the United States as separation of Church and State, was established by the federal Constitution and confirmed by the Supreme Court. It is however important to notice that the “wall of separation” – to use Thomas Jefferson's phrase – is a contested border, which is at the heart of an endless fight opposing the defenders of a radical secularization of the American society to those who consider that religion must play a greater role in political life.